Effects of Pipemidic Acid, Phenazopyridine HCL and Sodium Diclofenac on Pain Perception Following Endoscopic Urological Surgery: Double-blinded Randomized-Controlled Trial - Prahara Yuri; Zulfikar Ali; Nur Rasyid; Ponco Birowo (Acta Medica Indonesiana)
Aim: to evaluate the analgesic effect, the side effects and the safety of analgesics following endoscopic urological procedure. Methods: eighty patients who underwent endoscopic urological surgery at Kardinah Hospital, Tegal from June to July 2015 were divided into four groups. The experimental group was administered analgesic for 4 days pipemidic acid (A) 400 mg bid, or phenazopyridine (B) 200 mg tid, or sodium diclofenac (C) 50 mg bid and the control (D) group was administered placebo tid for 4 days. The analgesic effects were assessed using Visual Analog Scale (VAS). Association between variables was assessed using Cramers V and Kruskall Wallis. Results: the endoscopic urological procedures consisted of 30 patients for URS, 6 patients for lithotripsy, 17 patients for TURP, 24 patients for removal JJ stent and 3 patients for cystoscopy. The mean age of group A, B, C and D (control) was 50.1 (13.7), 50.7 (14.8), 49.1 (13.4), and 49.6 (14.3) years, respectively, and follow-up period was 7 days. The VAS score in all experimental groups was less than control group on day 1 to 7 following endoscopic urological procedures (p<0.05). In the experimental group, there was no difference between groups B and C (p>0.05). Group A demonstrated a more favourable analgesic effect than B and C (p<0.05). No serious side effects were detected in any of the cases. Conclusion: we conclude that oral analgesics are effective for pain relief following endoscopic urological surgery. Pipemidic acid was found to have a superior analgesic effect than phenazopyridine HCl and sodium diclofenac.